Quantitative Determination of L-Histidine HCl, L-Arginine HCl, Glycine, and Threonine in a Laboratory-Scale Sterile Formulation by UPLC - Bagus Ovi Pratama (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Establishing dependable analytical procedures is crucial for maintaining the quality of amino acid–based sterile formulations, particularly during early-stage development. Objective: This study describes the development and validation of an ultra-performance liquid chromatography (UPLC) method for the concurrent determination of L-Histidine HCl, L-Arginine HCl, Glycine, and Threonine in laboratory-scale preparations. Methods: The chromatographic system was optimized to produce distinct and symmetrical peaks, ensuring adequate resolution without interference from formulation components, solvents, or possible impurities.Validation of the proposed method was carried out based on widely accepted analytical criteria, including linearity, precision, accuracy, and assay evaluation. Result: The calibration curves exhibited strong linear relationships within the studied concentration ranges, with correlation coefficients (r) exceeding 0.98 for all compounds. Repeatability was demonstrated by relative standard deviation (RSD) values below 2%, indicating consistent analytical performance. Accuracy assessment through recovery experiments produced values approaching 100%, confirming the method’s reliability. Furthermore, assay results for each analyte were within the predefined acceptance range of 90%–110%.The analysis was completed within approximately 7 minutes, demonstrating the method’s efficiency for routine laboratory use. Conclusion: In summary, the developed UPLC method is precise, accurate, and suitable for simultaneous amino acid quantification in sterile formulation studies and quality control applications.